Феномен "Маски" и проблема коммуникативного конституирования человека в романе К. Абэ "Чужое лицо" - Нефедев, С.Н. (Культура народов Причерноморья, 2002)
The article is reflecting existential-pfenomenological analysis of the problem with locus on interhuman com-munication. Particular heed is dedicated to dialectical research of phenomenal and existential.